PENGARUH PENURUNAN PONDASI TIANG PANCANG AKIBAT DRAWDROWN (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2021)
The impact of the building’s foundation drop on its construction. In the field the decline is due to several factors, with underground erosion that leads to removal of the soil, a decrease in volume in the soil. In addition, the decline can be a ressult of vibrations, since it can cause the movement of small amounts of soil that fill the surrounding space, causing the voleme of the soil to drop. Identification is necessary to determine the cause of the foundation decline. The study aims to determine the underlying cause of the building’s fall. By physically identifying the soil on the ground in order to identify the soil support of the building load, the column’s reaction to the foundation of the stake, and the skin negative see if there is a reduction of the upward capacity on the long post covers. Research does not make it a problem to soil consulidate, as does the number of installed stakes as needed. However, with the reduction of the upward support of the blanket of the stake, the upward weight of 82.19 tons fell to 15.83 tons, while the emission of a permit waas 23.515 tons, it was due to the weight of the water around the foundation of the mizken pole.